FUNCTIONS PRESERVING CONNECTEDNESS OR PATH-CONNECTEDNESS - Shekutkovski, Nikita; Markoski, Gjorgji; Andonović, Beti (Matematichki Bilten, 2007)
We prove some theorems and give examples concerning functions preserving connectedness and functions preserving path connectedness.